High-dose-rate brachytherapy for vaginal cancer: Learning from treatment complications. Issue 1 (1st January 2002) - Tyree, W. C; Cardenes, H; Randall, M; Papiez, L
Abstract : Abstract: Tyree WC, Cardenes H, Randall M, Papiez L. High-dose-rate brachytherapy for vaginal cancer: learning from treatment complications. Historically, early stage vaginal cancer has been treated with low-dose-rate (LDR) brachytherapy with or without external beam radiation therapy (EBRT). Complication rates have been low and treatment efficacious. Although high-dose-rate (HDR) brachytherapy has been used for cervical cancer in many countries for over a decade, only more recently has it been integrated into treatment plans for vaginal cancer. This paper describes three patients treated with HDR brachytherapy who experienced significant late effects. Given the very limited amount of literature regarding the use of HDR brachytherapy in vaginal cancer, this analysis potentially contributes to an understanding of treatment-related risk factors for complications among patients treated with this modality. A focused review of hospital and departmental treatment records was done on three patients treated with HDR brachytherapy. Abstracted information included clinical data, treatment parameters (technique, doses, volume, combinations with other treatments) and outcomes (local control, survival, early and late effects). A review of the available literature was also undertaken. All patients had significant complications. Although statistical correlations between treatment parameters and complications are impossible given the limited number of patients, this descriptive analysis suggests that vaginal length treated with HDR brachytherapy is a risk factor for early and late effects, that the distal vagina has a lower radiation tolerance than the upper vagina with HDR as in LDR, and that combining HDR with LDR as done in our experience carries a high risk of late toxicity. Integration of HDR brachytherapy techniques into treatment plans for early stage vaginal cancers must be done cautiously. The etiology of the significant side effects seen here is likely to be multifactorial. For users of HDR brachytherapy in vaginal cancer, there is a need to further refine and standardize treatment concepts and treatment delivery. Ideally this will be based on continued careful observation and reporting of both favorable and unfavorable outcomes and experiences.